S20 Kbild scores have similar power to predict survival as pulmonary physiology in interstitial lung disease. (15th November 2016) - Sharp, C; Baggott, C; Birring, SS; Adamali, HI
Abstract : Background: The KBILD questionnaire is an ILD health related quality of life (HRQL) tool. Its relationship with survival has not been assessed. Aims: Assess impact of KBILD scores on survival in a heterogeneous population with interstitial lung disease (ILD). Methods: Patients attending the Bristol ILD service with fibrotic ILDs completed KBILD questionnaires, full lung function and exercise testing. Survival analysis using univariable and multivariable Weibull regression with an accelerated time-failure form was used to assess the significance of KBILD scores to predict all cause mortality. Comparison was made with lung function from the same clinic visit. Results are reported as hazard ratio and time ratio. Area under receiver operator characteristics (AUROC) curve analysis was used to assess sensitivity of KBILD for predicting 12-month mortality. Results: 175 patients, 58% IPF, 67.4% male, completed a KBILD questionnaire. Mean values were; age 71yrs, KBILD 61, FVC 84%, DLCO 50%, walk distance 292m. 48% had oxygen desaturation on 6-minute walk. 47 patients (26.9%) died. Mean follow-up was 19.8 months, median 14.4 months. 156 patients had >12 months follow-up and these were included in the prognostic evaluation. Univariable survival analysis showed age, KBILD, FVC, DLCO, walk distance and exertional desaturation to have prognostic significance for all cause mortality. Univariable analysis of the sub-categories of the KBILD score showed the psychological (p = 0.003) and breathlessness (p = 0.002) domains to be significant, while the chest symptoms domain was not (p = 0.269). After backwards stepwise selection the multivariable model contained age, KBILD, FVC and desaturation (Table 1 ). All included variables had prognostic significance. AUROC analysis showed KBILD had equivalent sensitivity for 12-month mortality to FVC, DLCO and better sensitivity than walk distance (c-statistic in Table 1 ). A KBILD score of 34 had 75% sensitivity for 12-month mortality, but only 10.5% specificity. Estimated median survival with KBILD of <34 was 9.7 months, compared to 36.4 months for KBILD > 34 (p = 0.02). Conclusions: In this cohort, the KBILD has equivalent prognostic power in ILD to pulmonary physiology and exercise testing at a single point in time. It is important to assess HRQL to give ILD patients optimal prognostic information.